Partial Metalation of Porphyrin Moieties in Hydrogen‐Bonded Organic Frameworks Provides Enhanced CO2 Photoreduction Activity. (3rd May 2022) - Zhang, An‐An; Si, Duanhui; Huang, Haibo; Xie, Lei; Fang, Zhi‐Bin; Liu, Tian‐Fu; Cao, Rong
Abstract: In natural photosynthesis, the architecture of multiproteins integrates more chromophores than redox centers and simultaneously creates a well‐controlled environment around the active site. Herein, we demonstrate that these features can be emulated in a prototype hydrogen‐bonded organic framework (HOF) through simply varying the proportion of metalated porphyrin in the structure. Further studies demonstrate that changing the metalloporphyrin content not only realizes a fine tuning of the photosensitizer/catalyst ratio, but also alters the microenvironment surrounding the active site and the charge separation efficiency. As a result, the obtained material achieves the challenging overall CO2 reduction with a high HCOOH production rate (29.8 μmol g −1  h −1, scavenger free), standing out from existing competitors. This work unveils that the degree of metalation is vital to the catalytic activity of the porphryinic framework, presenting as a new strategy to optimize the performance of heterogeneous catalysts. Abstract : A biomimetic catalyst for efficient overall CO2 photoreduction was developed through self‐assembling porphyrins into a hydrogen‐bonded organic framework. The combination of more photosensitizers than redox centers in the structure allows for not only the adequate photon input and efficient use of photogenerated charge, but noticeable changes to the microenvironment surrounding active sites.